2017
DOI: 10.5694/mja16.00597
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccination and genital warts in young Indigenous Australians: national sentinel surveillance data

Abstract: The known The Australian HPV vaccination program has led to significant declines in a number of HPV-related conditions, including diagnoses of genital warts in young women and heterosexual men at sexual health clinics.The new We found marked declines in the proportions of young Indigenous women and men attending sexual health clinics for the first time who were diagnosed with genital warts following introduction of the HPV vaccination program, similar to declines among non-Indigenous young women and men.The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
4
23
0
1
Order By: Relevance
“…In each jurisdiction, estimated HPV vaccination coverage of Indigenous students was much higher than reported in many countries, including the United States, New Zealand and France . This high level of coverage is consistent with findings of large falls in the prevalence of HPV and the incidence of genital warts in Indigenous people . The vaccine achieves strong herd protection even at relatively low coverage, and the benefits of vaccination were substantially augmented in Australia by the large scale catch‐up program .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In each jurisdiction, estimated HPV vaccination coverage of Indigenous students was much higher than reported in many countries, including the United States, New Zealand and France . This high level of coverage is consistent with findings of large falls in the prevalence of HPV and the incidence of genital warts in Indigenous people . The vaccine achieves strong herd protection even at relatively low coverage, and the benefits of vaccination were substantially augmented in Australia by the large scale catch‐up program .…”
Section: Discussionsupporting
confidence: 76%
“…A comprehensive analysis found the cervical screening participation rate in Queensland to be consistently much lower for Indigenous than non‐Indigenous Australian women aged 20–69 years during 2000–2011; further, high grade cervical abnormalities were detected more frequently and clinical investigation of abnormalities was slower . Prior to the HPV vaccination program, the prevalence of HPV types 16 and 18 was similar among Indigenous and non‐Indigenous women, consistent with findings that post‐vaccination reductions in the incidence of genital warts and in the prevalence of HPV infections have been similar for Indigenous and non‐Indigenous women …”
supporting
confidence: 59%
“…It is important to note that our analysis provides predictions across the entire Australian population, and the findings are not generalisable to specific population subgroups, such as Aboriginal and Torres Strait Islander women, migrants, or disadvantaged subpopulations. Although the effects of HPV vaccination in Australia appear to have been similar in Indigenous and non-Indigenous Australians 15,38 and across areas of different socioeconomic groups, 39 participation in screening differs by Indigenous status and area-level socioeconomic status. 4,40 Indigenous women are 2·5 times more likely to be diagnosed with cervical cancer, and 3·8 times more likely to die of the disease than non-Indigenous women.…”
Section: Discussionmentioning
confidence: 96%
“…In ambulatory patients, a study reported significant declines in presentations with genital warts among Aboriginal and Torres Strait Islander women aged 12-20 years and 21-30 years and males aged 12-20 years presenting to sexual health clinics between the two periods of 2004-2007 and 2008-2014 ( Figure 6 and 7). 38 Another study found large declines in hospitalisations 30,39,40 Cervical screening registers have not routinely received information about the Aboriginal and Torres Strait Islander status of women participating in screening. However, the decline seen in the Northern Territory, where 31% of the female population is Aboriginal and Torres Strait Islander, 41 is similar to that observed nationally ( Figures 8 and 9).…”
Section: Genital Wartsmentioning
confidence: 99%